Keloid-like Pilomatricoma of the Auricle: A Case Report and Review of Literature - Shinta Trilaksmi Dewi; Hanggoro Tri Rinonce; Kristiana Etnawati; Yohanes Widodo Wirohadidjojo (Karger Publishers, 2022)
Pilomatricoma is a rare benign skin adnexal tumor arising from hair matrix cells. It usually manifests as a firm-to-hard, well-circumscribed, nontender nodule often mistaken as a dermoid cyst. However, its clinical presentation has been reported to mimic keloid. In addition, although it occurs most frequently in the head and neck area, pilomatricoma is rarely reported on the auricle. Herein, we reported a case of pilomatricoma occurring on the posterior part of a 9-year-old girl's auricle. Unlike classic pilomatricoma, the tumor closely resembled a keloid. Nevertheless, histological examination following excision of the tumor revealed a dermal tumor arranged in solid nests consisting of basaloid and ghost cells along with foreign body reaction, calcification, and ossification, confirming the diagnosis of pilomatricoma. The rarity, atypical clinical presentation, and unique location of this tumor contributed to the misdiagnosis of this case. Therefore, we reviewed previous cases of pilomatricoma of the auricle reported in the literature to provide a comprehensive understanding of this rare entity.